2012
DOI: 10.1108/01443581211245919
|View full text |Cite
|
Sign up to set email alerts
|

The present value model and Thailand's current account balance

Abstract: Purpose -The purpose of this paper is to determine whether current account imbalancessurpluses or deficits -are "excessive" and hence constitute a valid concern. The second objective is to assess the degree of capital mobility by comparing the variance of the current account derived from the intertemporal model with that of the actual current account. Design/methodology/approach -The paper addresses the issues by constructing the intertemporal model using annual data between 1960 and 2006. The authors applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Ca' Zorzi and Rubaszek (2012) found an intertemporal model to explain current account configuration in the euro area. Baharumshah and Ismail (2012) concluded that present value of future net output reflects current account evolution in Thailand. Luo et al (2012) incorporated two types of uncertainty to improve model's predictions for current account persistence in small open economies.…”
Section: Introductionmentioning
confidence: 99%
“…Ca' Zorzi and Rubaszek (2012) found an intertemporal model to explain current account configuration in the euro area. Baharumshah and Ismail (2012) concluded that present value of future net output reflects current account evolution in Thailand. Luo et al (2012) incorporated two types of uncertainty to improve model's predictions for current account persistence in small open economies.…”
Section: Introductionmentioning
confidence: 99%
“…Chirathivat and Malikamas (2010) state that Thailand has been affected by the U.S. sub-prime crisis. Baharumshah and Ismail (2012) report the close correlation between changes in the current account and the present value of future net output based on a VAR model. Examining the SET index, Chokesirikuchai et al (2013) confirm the sensitivities of the interactions between the stock index and exchange rate and between the interest rate and inflation rate.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Examples of the application of the model include Kim et al (2006) based on data from New Zealand, Adedeji (2001) on Nigerian data, Agénor et al (1999) on French data, Apergis et al (2000) on Greece data, Bergin and Sheffrin (2000) on Australian, Canadian, and United Kingdom data, and Cashin and McDermott (1998) on Australian data. In the context of ASEAN countries, only a few researchers in the literature would be found and include Guest (1999), Guest and McDonald (1999), Hussein and de Mello(1999), Ostry (1997), Milesi-Ferretti and Razin (1996) and more recently Baharumshah and Ismail (2012). The following discussion demonstrates and highlights some important aspects and econometric implications of the theoretical model when applied to countries under study.…”
Section: Theoretical Frameworkmentioning
confidence: 98%